2018
DOI: 10.1520/mpc20170169
|View full text |Cite
|
Sign up to set email alerts
|

Surface Layer Characterization of Shot Peened Gear Specimens

Abstract: The production of gear components includes numerous manufacturing operations, which are carried out to ensure proper surface characteristics. Shot peening is one of the surface finishing processes used for transmission components like gears to improve their fatigue behavior. Shot peening increases the compressive residual stresses on the surface, and the procedure also reduces the amount of retained austenite in the surface layer. In addition, shot peening has an influence on other mechanical properties, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…5, the surface roughness Ra of SP5 is about 21.28% less than that of SP1, whereas the reduction is about 7.15% for Rz. It is revealed that proper increase of coverage can reduce the surface roughness of gear tooth flanks, and the results are compatible with that of other literature [10,17,34,39].…”
Section: Surface Roughnesssupporting
confidence: 90%
See 4 more Smart Citations
“…5, the surface roughness Ra of SP5 is about 21.28% less than that of SP1, whereas the reduction is about 7.15% for Rz. It is revealed that proper increase of coverage can reduce the surface roughness of gear tooth flanks, and the results are compatible with that of other literature [10,17,34,39].…”
Section: Surface Roughnesssupporting
confidence: 90%
“…Such damages created by overlapping of peening dimples and surface plastic deformation can often be found around the hobbing marks or between dimple boundaries, which could cause premature crack initiation on tooth flanks. Some researchers also got the similar SEM characterization observations on other materials [10,[41][42][43][44][45][46][47]. To conclude, it is inevitable that defects generate on the peened surface of gears as clearly seen in the SEM images.…”
Section: Microtopographysupporting
confidence: 52%
See 3 more Smart Citations